Validation of Romanowsky staining as a novel screening test for the detection of faecal cryptosporidial oocysts - Brar, A. P. S. (J Parasit Dis, 2016)
Cryptosporidiosis is an emerging waterborne protozoan disease and one of the major causes of neonatal diarrhea in humans and animals. But the disease remains under diagnosed due to lack of availability of special stains in majority of laboratories at primary health centers. Therefore, it requires a rapid screening test for routine diagnosis in conventional laboratory set up. In this pursuit, the present study was planned. During this study, fecal samples from 100 representative animals randomly selected from 17 out breaks of bovine calf diarrhea, were stained with modified Ziehl Neelsen staining (mZN) and Leishman’s stain to demonstrate cryptosporidial oocysts and for routine fecal examination, respectively. By mZN staining, 25 cases confirmed the presence of cryptosporidial oocysts. However, examination of Leishman’s stained fecal smears revealed round hollow unstained bodies resembling cryptosporidia in 20 cases. Therefore, a comparative morphometric analysis was made between the two techniques to determine their relative efficacy in demonstrating cryptosporidia in the feces of affected animals. The analyses showed that the Leishman’s stain can be effective in making a presumptive diagnosis of cryptosporidiosis with a little experience. Confirmation of cryptosporidiosis was done by histopathological examination of intestinal sections of calves died during these out breaks. The findings appear to have great clinical value for routine laboratory screening of fecal samples for cryptosporidiosis as conventional Romanowsky stains are readily available and used for multipurpose examination in most of the laboratories at grass root level. Perusal of literature proved this to be the first attempt at easy diagnostics for cryptosporidiosis.